Prinsip Keadilan dalam Pasar Bebas : Peran Hukum Menjamin Itikad Baik dalam Transaksi Bisnis Internasional - Gusti Komang Trisna Fijayanti (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2026)
This study aims to analyze the position and function of the principle of good faith in the international contract law system and analyze its role in providing legal protection for parties in international business transactions, especially in the context of the free market era. This study uses a normative juridical method with a statutory and conceptual approach to examine the legal provisions related to this principle. The results of the study indicate that the principle of good faith is not only understood as a moral value in contractual relations, but has also developed into a legal norm recognized in various international legal instruments, such as the UNIDROIT Principles of International Commercial Contracts, Principles of European Contract Law (PECL), and the United Nations Convention on Contracts for the International Sale of Goods (CISG). This principle includes subjective aspects in the form of honest intentions of the parties and objective aspects in the form of internationally applicable fairness standards. The principle of good faith plays an important role in the formation, implementation, and resolution of international business contract disputes. Although there are differences in acceptance between civil law and common law systems, the application of this principle can be harmonized through international legal instruments and soft law. Thus, the principle of good faith is an important basis for realizing fair, balanced and sustainable international business transactions.